Evidence Base within Clinical Practice In Modern Medicine (A Clinicians Perspective) - Cobb, William James (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The aim of this work is to critically assess to what extent and in what ways evidence basedpractice may, or indeed may not, assist clinical practitioners to avoid confusing personalopinion with evidence. “We become confident in our educated guesswork to the point where itis easy to confuse personal opinion with evidence or personal ignorance with genuine scientificuncertainty” (Naylor 1995). The author of this work is a clinician currently practising in thearea of acute and emergency and trauma healthcare, and therefore clinical treatments will beconsidered in the context of evidence based practice. This work has been formulated aroundan online postgraduate Master’s module investigating the meaning of evidence based practicein the modern healthcare setting. Some of the content of this work will draw upon the learningobjectives of the evidence based module by using examples of online forum discussions, whichtook place during the module between various clinical practitioners. It is a further expectationof this work to examine to what extent and in what ways evidence based practice assistsclinicians in making research based clinical decisions, whilst considering how evidence is orindeed is not amalgamated into clinical practice. Evidence and the concepts used to cementevidence into practice will be explored both by considering the online forum discussions thattook place during the module, and again by looking at current research and literature to drawcomparisons and extract ideas.